2022
DOI: 10.1002/lno.12286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marine heat waves on carbon metabolism, optical characterization, and bioavailability of dissolved organic carbon in coastal vegetated communities

Abstract: Dissolved organic carbon (DOC) plays an essential role in the global marine carbon cycle, with coastal vegetated communities as important DOC producers. However, the ultimate fate of this DOC remains still largely unknown due to the lack of knowledge about its chemical composition and lability. Furthermore, global change could alter both DOC fluxes and its bioavailability, affecting the carbon sequestration capacity of coastal vegetated communities. This study explores, in two contrasting seasons (winter and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Therefore, the effects of heatwave depend on their intensity and duration (Saha et al 2020). Temperature increases can benefit aquaculture seaweeds but only if within their thermal tolerance window (Egea et al 2022). For instance, a seawater temperature rise from 20 C to 24 C can enhance growth of G. lemaneiformis (Liu et al 2018) but an increase from 25 C to 30 C reduces its growth (Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effects of heatwave depend on their intensity and duration (Saha et al 2020). Temperature increases can benefit aquaculture seaweeds but only if within their thermal tolerance window (Egea et al 2022). For instance, a seawater temperature rise from 20 C to 24 C can enhance growth of G. lemaneiformis (Liu et al 2018) but an increase from 25 C to 30 C reduces its growth (Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have documented the impacts of marine heatwaves on DOC excretion by seaweeds and its use by phycosphere bacteria. Egea et al (2022) found that simulated marine heatwaves in summer did not affect net community productivity dominated by the macroalga Caulerpa prolifera but decreased DOC daily fluxes and increased the proportion of RDOC. However, the potential mechanisms remain unknown.…”
mentioning
confidence: 99%
“…The sediment organic carbon (OC) stock found in upper sediments was in the same range than those reported for Cadiz Bay habitats by de los Santos et al (2023), and similar to those reported by Bañolas et al (2020) for seagrasses and by Holmer et al (2004) for the macroalgae. This high sediment OC stock is explained by the high macrophyte density and fine grain sizes, which feature the donor sampling area (de los Santos et al, 2023;Egea et al, 2023b).…”
Section: Decreasing Sediment Oc Stocks By Remineralizationmentioning
confidence: 99%
“…A significant fraction of this DOC is formed by bioavailable material (i.e., the labile fraction; DOC L ) being an important driver of secondary production, acting as a quick transfer of carbon across the food web (Egea et al, 2019;Moran et al, 2022). Otherwise, another fraction of this DOC is apparently non-accessible to rapid microbial degradation (i.e., recalcitrant fraction; DOC R ) and it can be exported and sequestered in the deep ocean, and therefore it is considered nowadays a cornerstone in the contribution of oceans to carbon sequestration (Krause-Jensen and Jimeńez-Ramos et al, 2022;Zhang et al, 2023;Egea et al, 2023b). On the other hand, seagrass and macroalgae are highly variable in terms of size, biomass, and meadow canopy complexity, which ultimately affect the properties of sediment deposits -main OM origin (autochthonous vs allochthonous), dry bulk density (DBD), OC and CaCO 3 contents, etc (Mazarrasa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While conducting experimental work in situ, especially in the subtidal, is accompanied by a number of logistical difficulties, conducting heating experiments is particularly demanding since heating the marine environment requires an exceptional amount of energy due to the high thermal conductivity of water. The most recent and notable advance has been achieved by placing small rigid cylinders with gas‐permeable plastic bags and 100 W heaters connected to the battery of a boat for 110 h in a shallow seagrass meadow, resulting in a 3°C above ambient water temperature (Egea et al 2023). The gas‐permeable, flexible bags enabled an oxygen exchange to avoid unnatural concentrations, for example, oversaturation during light hours and anoxia during dark hours, and were claimed to prevent water stagnation through hydrodynamic forcing.…”
mentioning
confidence: 99%